Control Psicológico Parental y Problemas Internalizados y Externalizados en Adolescentes de Lima Metropolitana [Article] - Solis Calcina, G.L. (2019)
The paper presents the results of a study of the relation between parental psychological control and the internalized and externalized problems of a group of 170 adolescents (58.2 % males), between the ages of 13 and 17, from a private school in Lima, Peru. The Dependency-Oriented and Achievement-Oriented Psychological Control Scale (DapCS-S) and the Youth Self Report (ySR) inventory were used. Findings showed a positive and significant correlation between Achievement-Oriented Parental Psychological Control (apC) and Dependency-Oriented Parental Psychological Control (DpC) and the internalized and externalized problems. Results also showed that the maternal DpC and the paternal apC explain significantly the adolescents’ internalized problems. On the other hand, the maternal and paternal DpC explain significantly the adolescents’ criminal conduct.